Optimasi Distribusi Pencahayaan Alami Terhadap Kenyamanan Visual Pada Toko “Oen” Di Kota Malang - Andrew Setiawan (Intra, 2013)
Natural lighting is one of the light sources is very important for humanity, including natural lighting is also required to perform the activity. With appropriate lighting then our activities will not be disrupted, but the size of the sun is always different in each location, but it must have a standard retail lighting that can keep visitors comfortable when under any circumstances. This study was conducted to determine the size distribution of sunlight lighting the comfort of visitors.The method in use is descriptive qualitative, analysis by comparing the situation in the field, literature and simulation. The results showed that the lux value that already meet the standard, but there is still light distribution uneven that it needs assistance in order to be equitable. Desktop Radiance simulation is used as a simulation of natural lighting.